Analysis of an improved Nishihara creep model considering plastic strain accumulation - Cheng, Yang; Zhang, Liangliang (Frontiers in Materials, 2023)
Rock-engineering structures, particularly subway excavation rock engineering structures, are subjected to the long-term effects of external loading that may gradually damage and cause creep and severe plastic deformations or even progressive failure. The traditional Nishihara creep model cannot accurately describe the accelerated creep stage of rock with particularly obvious nonlinear characteristics. Based on this model, a damage variable that can consider the plastic strain accumulation is introduced in this study to replace the viscoplastic body in the traditional model with a damage viscoplastic body and es-tablish an improved Nishihara creep model. Using the superposition principle, the creep equations of the improved model in the one- and three-dimensional stress states are derived. The accuracy and rationality of the improved model are verified using uniaxial and conventional triaxial creep tests under different confining pressures. The improved model can not only accurately reflect the nonlinear characteristics of the creep curve in the decay and constant velocity stages but also describe the accelerated creep characteristics of sandstone in a high-stress state. Its applicability and accuracy are superior to those of the traditional model. This study can provide a theoretical reference for subway tunnel excavation and stability analysis of deep roadway surrounding rocks.